Pengaruh Kompetensi Dan Karakteristik Individu Terhadap Kinerja PNS di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Serdang Begadai - Maulia Agustina; Melisa Zuriani Hasibuan (Forum Kerjasama Pendidikan Tinggi, 2020)
This study aims to determine the influence of the relationship of competence and individual characteristics to the performance of Civil Servants in the Population and Civil Registration Office of Serdang Bedagai Regency. The population in this study were all employees in the Department of Population and Civil Registration of Serdang Bedagai Regency with a total of 50 employees and a sample determination technique with saturated samples, so the sample amounted to 50 employees. The data analysis technique that I use in this research is quantitative descriptive. The results of this study were obtained from the regression equation Y = 18.602 + 0.194 X1 + 0.394X2 + e. Constant value (a) of 18,602 indicates that if the competency variable (X1) and individual characteristics (X2) value is 0, then the employee's performance is 18,602. The variable regression coefficient X1 of 0.194 indicates that the competency variable (X1) influences employee performance and X2 variable of 0.394 individual characteristics (X2) influences employee performance. The partial test results of competency variables (X1) and Characteristics (X2) have a positive and significant effect on employee performance in the Population and Civil Registration Service in Serdang Bedagai Regency where the value of t count> t table (2,288> 1,677) Competency Variables (X1) and (3,399> 1,677) Individual Characteristics variable (X2) with a significant level of 0,000 <0.05. The R square value obtained is 0.870. Then it can be seen the influence of variables X1, X2 on Y variables by calculating the coefficient of determination = R2 x 100% = 87.0%. The figure shows that the influence of variable X1 (Competence), Individual Characteristics (X2) on Variable Y (Employee Performance) is 87.0% and the remaining 13% is influenced by other variables not in this study